Soil Carbon, Nitrogen, and Phosphorus Cycling Microbial Populations and Their Resistance to Global Change Depend on Soil C:N:P Stoichiometry - Gongwen Luo; Chao Xue; Qianhong Jiang; Yan Xiao; Fengge Zhang; Shiwei Guo; Qirong Shen; Ning Ling (mSystems, 2020)
ABSTRACT Maintaining stability of ecosystem functions in the face of global change calls for a better understanding regulatory factors of functionally specialized microbial groups and their population response to disturbance. In this study, we explored this issue by collecting soils from 54 managed ecosystems in China and conducting a microcosm experiment to link disturbance, elemental stoichiometry, and genetic resistance. Soil carbon:nitrogen:phosphorus (C:N:P) stoichiometry imparted a greater effect on the abundance of microbial groups associated with main C, N, and P biogeochemical processes in comparison with mean annual temperature and precipitation. Nitrogen cycling genes, including bacterial amoA-b, nirS, narG, and norB, exhibited the highest genetic resistance to N deposition. The amoA-a and nosZ genes exhibited the highest resistance to warming and drying-wetting cycles, respectively. Soil total C, N, and P contents and their ratios had a strong direct effect on the genetic resistance of microbial groups, which was dependent on mean annual temperature and precipitation. Specifically, soil C/P ratio was the main predictor of N cycling genetic resistance to N deposition. Soil total C and N contents and their ratios were the main predictors of P cycling genetic resistance to N deposition, warming, and drying-wetting. Overall, our work highlights the importance of soil stoichiometric balance for maintaining the ability of ecosystem functions to withstand global change. IMPORTANCE To be effective in predicting future stability of soil functions in the context of various external disturbances, it is necessary to follow the effects of global change on functionally specialized microbes related to C and nutrient cycling. Our study represents an exploratory effort to couple the stoichiometric drivers to microbial populations related with main C, N, and P cycling and their resistances to global change. The abundance of microbial groups involved in cellulose, starch, and xylan degradation, nitrification, N fixation, denitrification, organic P mineralization, and inorganic P dissolution showed a high stoichiometry dependency. Resistance of these microbial populations to global change could be predicted by soil C:N:P stoichiometry. Our work highlights that stoichiometric balance in soil C and nutrients is instrumental in maintaining the stability and adaptability of ecosystem functions under global change.